PEMBIAYAAN MUSYARAKAH DI PT. BPR SYARIAH AL-MAKMUR LIMBANANG - Intan Purnama Sari; Rizal Rizal; Rizal Fahlefi (Tamwil, 2019)
This study aims to describe and understand the system of profit sharing for musyarakah financing. This study uses a qualitative descriptive type and field study research method by conducting interviews and documentation. The results of the study show that the profit sharing system applied by PT. BPR Syariah Al-Makmur uses revenue sharing, with profit sharing for banks calculated from the results of financing given divided by the total value of the project and multiplied by the estimated profit sharing ratio. The researcher concluded that the profit sharing system of Islamic banks as a whole was in accordance with the rules. The researcher suggested that banks use a profit sharing system, with the burden of costs being borne by banks and customers, so that there is a form of justice in musyarakah financing